THE EFFECT OF PROFITABILITY AND CAPITAL STRUCTURE ON SHARE PRICES IN PROPERTY AND REAL ESTATE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) PERIOD 2015-2018) - Nizari, Yosi Nabila; Sidik, Solihin (Jurnal Ekonomi Balance, 2018)
The purpose of this research is to view, analyze and analyze the effects of partial and simultaneous profitability and equity structure. The independent variables used in this study are the profitability with the proxy return on equity (ROE) and the capital structure with the proxy debt-to-equity ratio (DER), while the dependent variable in this research is the stock price. The population in this study is stock prices. The population of this study is the real estate and real estate companies listed on the Indonesian stock exchange from 2015 to 2018. The sampling technique used is purposeful sampling. The methods used in this study are descriptive and confirmatory methods. The data analysis results based on empirical research are as follows: (1) Partially profitability has a significant positive effect in share prices in property and real estate companies in the study period, capital structure partially has a significant positive effect on stock prices of property and real estate companies in the study period. (2) Profitability (ROE) and Capital Structure (DER) have a positive and significant effect on share prices of property and real estate companies in the study period